AN ANALYSIS OF COMPOUNDING AND CLIPPING SLANG WORDS FOUND IN “AFTER WE COLLIDED” MOVIE - Ni Putu Rahmania Ayu Kasitha; Putri Gita Ardiantari Ida Ayu (SPHOTA: Jurnal Linguistik dan Sastra, 2022)
Abstract The research aimed to determine types of slang words and analyze compounding and clipping types of slang words that used in "After We Collided" movie. Yule's (1986) theory was used to determine the types of compounding and clipping. Leech's (1981) theory to analyzed the meaning of slang words found in "After We Collided" movie. The descriptive qualitative method was used in this study. Several steps that were done in collecting the data involved watching the movie to understand the story, reading the movie script, selecting and taking notes, and the last step is classifying the data. The researcher found out seven data as compounding, and eleven data found as clipping. With the percentage, compounding 39% and clipping 61%. There are six data classified in conceptual meaning, only one data determined as connotative meaning, one data as affective meaning, and eleven data categorized in social meaning. With the percentages social meaning 34%, connotative meaning 5%, social meaning 61%, and affective meaning 5%. Keyword: slang word, meaning, movie. Abstrak Penelitian ini bertujuan untuk mengetahui jenis-jenis kata slang dan menganalisis jenis-jenis kata slang compounding dan clipping yang digunakan dalam film “After We Collided”. Teori Yule (1986) digunakan untuk menentukan jenis compounding dan clipping. Teori Leech (1981) untuk menganalisis makna kata-kata slang yang ditemukan dalam film “After We Collided”. Metode deskriptif kualitatif digunakan dalam penelitian ini. Beberapa langkah yang dilakukan dalam pengumpulan data meliputi menonton film untuk memahami cerita, membaca naskah film, memilih dan mencatat, dan langkah terakhir adalah mengklasifikasikan data. Peneliti menemukan tujuh data sebagai compounding, dan sebelas data ditemukan sebagai clipping. Dengan prosentase, compounding 39% dan clipping 61%. Ada enam data yang diklasifikasikan dalam makna konseptual, hanya satu data yang ditentukan sebagai makna konotatif, satu data sebagai makna afektif, sebelas data dikategorikan dalam makna sosial. Dengan persentase makna sosial 34%, makna konotatif 5%, makna sosial 61% dan makna afektif 5%. Kata kunci: kata slang, makna, film.